The Influence of Leadership Style, Organizational Culture, and Rewards on Employee Performance - Claudius Aprilianus Sot; Wahju Wulandari; Dharmayanti Pri Handini (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
For employees, organizational culture consists of a variety of implementation guidelines to technical guidelines. Every leader has his or her own passionate leadership style. Effective leadership requires the ability to adapt to various situations. When employees receive adequate compensation, performance will usually increase, but if compensation is inadequate, employee performance may decrease. This research has the aim of knowing whether the compensation given to employees is equal to the responsibility for their performance. The compensation indicator raises the enthusiasm of employees, how not, with the compensation of employees will be more prosperous. This study chose descriptive and quantitative methods. The results showed that leadership style, organizational culture, and simultaneous and partial rewards had a significant effect on employee performance, obtained from a significance value of 0.037, 0.025, and 0.003. The significant value is greater than alpha (0.000 < 0.05).